Pembelajaran Berbasis Literasi dan Numerasi dalam Meningkatkan Hasil Belajar Tematik di SD/ MI - Nur Faizah, Wela; Via Rahmawati , Alif; Yulia Putri , Adila; Rahma Maulidia, Alfiana; Damayanti , Risma; Suttrisno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Literacy and numeracy-based learning in thematic learning plays an important role in improving student learning outcomes. Numeracy literacy in thematic learning involves integrating the ability to read, understand and use numbers and mathematical concepts in the context of the themes studied, so that students not only memorize material but are also able to solve real problems in everyday life. The application of literacy and numeracy-based learning will foster student motivation in understanding the material and being able to apply it in various subjects. Literacy and numeracy skills of elementary school students in Indonesia are still low. Therefore, effective education is needed to improve student learning outcomes. The purpose of this study is to examine the effectiveness of literacy and numeracy-based learning in improving thematic learning outcomes of elementary/middle school students. The research method is based on a systematic literature study with data collection from relevant journals, books and scientific articles. The results show that learning will have a positive impact on students' thematic learning outcomes by integrating literacy and numeracy learning with various subjects in relevant and contextual themes, facilitating the development of critical thinking and real problem solving skills.